Implementation and Operational Research: Impact of a Systems Engineering Intervention on PMTCT Service Delivery in Côte d'Ivoire, Kenya, Mozambique. (1st July 2016) - Rustagi, Alison Silvis; Gimbel, Sarah; Nduati, Ruth; Cuembelo, Maria de Fatima; Wasserheit, Judith N.; Farquhar, Carey; Gloyd, Stephen; Sherr, Kenneth
Abstract : Background: Efficacious interventions to prevent mother-to-child HIV transmission (PMTCT) have not translated well into effective programs. Previous studies of systems engineering applications to PMTCT lacked comparison groups or randomization. Methods: Thirty-six health facilities in Côte d'Ivoire, Kenya, and Mozambique were randomized to usual care or a systems engineering intervention, stratified by country and volume. The intervention guided facility staff to iteratively identify and then rectify barriers to PMTCT implementation. Registry data quantified coverage of HIV testing during first antenatal care visit, antiretrovirals (ARVs) for HIV-positive pregnant women, and screening HIV-exposed infants (HEI) for HIV by 6–8 weeks. We compared the change between baseline (January 2013–January 2014) and postintervention (January 2015–March 2015) periods using t -tests. All analyses were intent-to-treat. Results: ARV coverage increased 3-fold [+13.3% points (95% CI: 0.5 to 26.0) in intervention vs. +4.1 (−12.6 to 20.7) in control facilities] and HEI screening increased 17-fold [+11.6 (−2.6 to 25.7) in intervention vs. +0.7 (−12.9 to 14.4) in control facilities]. In prespecified subgroup analyses, ARV coverage increased significantly in Kenya [+20.9 (−3.1 to 44.9) in intervention vs. −21.2 (−52.7 to 10.4) in controls; P = 0.02]. HEI screening increased significantly in Mozambique [+23.1 (10.3 to 35.8) in intervention vs. +3.7 (−13.1 to 20.6) in controls; P = 0.04]. HIV testing did not differ significantly between arms. Conclusions: In this first randomized trial of systems engineering to improve PMTCT, we saw substantially larger improvements in ARV coverage and HEI screening in intervention facilities compared with controls, which were significant in prespecified subgroups. Systems engineering could strengthen PMTCT service delivery and protect infants from HIV. Abstract : Supplemental Digital Content is Available in the Text.